Online Social Networking, Interactions, and Relations: Students at the University of the Free State, Bloemfontein - Sele, Sello J.; Coetzee, Jan K.; Elliker, Florian; Groenewald, Cornie; Matebesi, Sethulego Z. (Qualitative Sociology Review, 2019)
Online social networking (OSN) is an activity performed through social network sites (SNS) such as Facebook, Twitter, WhatsApp, and Instagram. OSN has become a dominant interaction mechanism within contemporary society. Online platforms are woven inextricably into the fabric of individuals’ everyday lives, especially those of young adults. We present a mixed-methods study—conducted at the University of the Free State in Bloemfontein—that analyzes how students reflect on their everyday experiences of OSN. The key theoretical frameworks guiding this research are phenomenology, existentialism, and reflexive sociology. These theoretical lenses collectively assist in broadening our understanding of the students’ experiences that reveal the complexities associated with their interactions and social relations via SNS. From their narratives we learn how the students make sense of their engagements on SNS, how these engagements have an impact on their social interactions, and how OSN affects their self-presentation.